2016
DOI: 10.1093/jamia/ocw123
|View full text |Cite
|
Sign up to set email alerts
|

Assessing electronic health record phenotypes against gold-standard diagnostic criteria for diabetes mellitus

Abstract: Researchers using EHR-based phenotype definitions should clearly specify the characteristics that comprise the definition, variations of ADA criteria, and how different phenotype definitions and components impact the patient populations retrieved and the intended application. Careful attention to phenotype definitions is critical if the promise of leveraging EHR data to improve individual and population health is to be fulfilled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…This need is particularly relevant to the success of studies such as the PMI All of Us Research Program, 10 other national research initiatives, 27,28 the future of CVD epidemiology, 35 and the development of learning healthcare systems. 7 Although several studies have evaluated the different dimensions of EHR data quality and developed EHR phenotyping algorithms, 16,2932 they frequently are from a single healthcare institution and use data from clinical care as a gold standard reference, including paper charts, patient and physician interviews, standardized patient encounters, registry data, and claims data. 23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This need is particularly relevant to the success of studies such as the PMI All of Us Research Program, 10 other national research initiatives, 27,28 the future of CVD epidemiology, 35 and the development of learning healthcare systems. 7 Although several studies have evaluated the different dimensions of EHR data quality and developed EHR phenotyping algorithms, 16,2932 they frequently are from a single healthcare institution and use data from clinical care as a gold standard reference, including paper charts, patient and physician interviews, standardized patient encounters, registry data, and claims data. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, national research consortiums, such as eMERGE (electronic medical records and genomics) Network, the NIH Collaboratory, and other research groups, have developed, tested, and validated EHR detection algorithms for various cardiovascular disease risk factors and events, including diabetes, HTN, heart failure, and coronary heart disease. 16,31,32 Many of these algorithms are developed at a single center, tested at other centers, and adapted if needed. 30 Consistent with prior studies, our results underscore the additive value of clinical data to ICD codes in case detection, especially for obesity, which has previously been reported as under-detected in administrative databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large well‐designed observational studies can help identify the benefits and harms of specific treatments among patients with T2DM, particularly among those who may be underrepresented in clinical trials (ie, the elderly and those with certain comorbidities such as heart and renal disease) . The identification of patients with T2DM from EHR and administrative databases has been conducted extensively in the prior literature …”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have identified and studied patients with T2DM using EHR and administrative databases within well‐defined but single data systems. However, less is known about the implementation of those strategies across diverse systems and at a large scale . Therefore, T2DM represented an optimal condition for us to construct, characterize and validate a cohort of patients with T2DM across four diverse PCORnet sites to determine the utility of using these integrated data to conduct epidemiological and comparative effectiveness research.…”
Section: Introductionmentioning
confidence: 99%